Association between 14 candidate genes, PM2.5, and affective disorders: a study of the Taiwan Biobank - Kai-Jie Ma; Yi-Ju Lin; Chiu-Shong Liu; Pei-Ying Tseng; Shi-Heng Wang; Chi-Yu Yao; Jong-Yi Wang (BMC, 2023)
Abstract Background Most studies have focused on the risk factors, treatment, and care of affective psychosis, and several have reported a relationship between ambient air quality and this psychosis. Although an association has been reported between psychosis and genes, studies mainly explored the associations between one type of psychosis and one gene; few have identified genes related to affective psychosis. This study investigates the genetic and environmental factors of affective psychosis. Methods In this retrospective longitudinal study, 27 604 participants aged 30-70 were selected from Taiwan Biobank. The participants' propensity scores were calculated based on their demographic information, and propensity score matching was performed to divide the participants into an experimental (i.e., affective psychosis) and control group at a 1:5 ratio. Plink was used to analyze the major and minor types of gene expression related to affective psychosis, and PM2.5 exposure was incorporated into the analyses. Results According to the generalized estimating equation analysis results, 8 single nucleotide polymorphisms (SNPs) belonging to the ANK3, BDNF, CACNA1C, and GRID1 genotypes were significantly correlated with depressive disorder (P < .001), with the majority belonging to the ANK3 and CACNA1C. A total of 5 SNPs belonging to the CACNA1C, GRID1, and SIRT1 genotypes were significantly correlated with bipolar disorder (P < .001), with the majority belonging to the CACNA1C. No significant correlation was identified between ambient air pollution and affective psychosis. Conclusions CACNA1C and GRID1 are common SNP genotypes for depressive disorder and bipolar disorder and should be considered associated with affective psychosis.